Intervenção da OTAN nos Bálcãs: um estudo de caso sobre a redefinição da regra da soberania implícita nos esforços de ordenamento e estabilização - Gonçalves, Daniela Norcia (2009)
The process of disintegration of the Yugoslavia has immensely attracted international attention as by its violent character and for showing that the hopes of peace and international stability of the post-Cold War were an illusion as by the reflections around the conflict itself and about themes co-related to the limits of both International Order and System and the function of the states. Studying this experience is very relevant for evaluating the meaning of international interventions and its consequences. The present research analyses the question f the sovereignty having as a case study the Balkans crisis during de 1990´s as a result to Tito´s death and the collapse of the region after the Cold War. It talks about the history of the region, the interventions occurred in the 1990´s, the creation of the International Criminal Court and OTAN´s action in Kosovo. It will rises two important points: the practice of humanitarian intervention that, undoubtedly, imply in a reinterpretation of the sovereignty as a society´s central regulator principle; and the problems resulted from the processes of (re) construction of the states during the post- Cold War